PROPAGANDA DALAM FILM (Analisis Teknik Propaganda Anti-Iran dalam Film Argo) - M Alif Mahmudi (Profetik: Jurnal Komunikasi, 2013)
Film is a medium that can affect people and share knowledge, ideology, and new discourses. Film became a significant medium to educate the public about what we understand and what we believe . Unique effect contained in the film makes the audience unconsciously receive new stimuli, either in the form of knowledge, ideology, and various other things. Then the audience believe and justify the values that exist in the film, unconsciously. In the contex of propaganda, many people use film advantages to spread their views and beliefs. As we can see in the Hitler regime in Germany, which even has a special minister of propaganda spread Hitler 's views to the public in various ways including by the film. The current movie, such as Argo, allegedly used the same way to spread ideas that contain propaganda purposes. This study is an attempt to read the movie Argo, which in fact saves controversy, especially in the sphere of propaganda. Some believe Argo is a series of anti - Iranian propaganda embodied in the movie. This study explores how the propaganda into the Argo, and how to deliver their propaganda messages.